Unveiling MRI-based structural phenotypes in temporomandibular joint osteoarthritis: implications for clinical practice and research - Ricardo de Souza TESCH; Thayanne Brasil Barbosa CALCIA; Diego DE NORDENFLYCHT (Dental Press Editora, 2024)
ABSTRACT Introduction: Osteoarthritis (OA) is a progressive degenerative disease characterized by the gradual degradation of cartilage, remodeling of subchondral bone, synovitis, and chronic pain. This condition impacts various large and small joints, including the temporomandibular joint (TMJ). However, addressing OA, particularly in impeding or reducing disease progression, is challenging due to its clinical and imaging heterogeneity. Authors are increasingly suggesting that this heterogeneity involves different phenotypes or subpopulations, discernible by variations in the disease's pathophysiology and structural manifestations. Even within the TMJ, these phenotypes may display distinct clinical features, laboratory parameters, biochemical markers, and imaging criteria. Recent research has proposed MRI as a reference standard for TMJ OA, highlighting its substantial agreement with histopathological changes. MRI-based phenotypes offer a promising avenue for understanding disease progression and treatment response, potentially providing valuable insights for prognosis and treatment planning. Objective: This article introduces the ROAMES-TMJ (Rapid OsteoArthritis MRI Eligibility Score for TMJ) to assess the structural eligibility of individuals for inclusion in TMJ OA clinical trials.